Corporate governance, capital structure and dividend policy - Mardani, Ronny Malavia (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
Corporate governance, capital structure and dividend policy are currently widely debated in finance. This research examines the influence of corporate governance and capital structure on dividend policy. This research also includes growth, profitability and firm size as independent variables. The samples in this research were manufacturing companies on the Indonesia Stock Exchange from 2012 to 2022. Based on the established criteria, a total of 38 companies were obtained. The data analysis technique was carried out using multiple linear regression. The results of the analysis show that corporate governance and profitability have a significant positive effect on dividend payout, which indicates that companies with good governance and profitable companies will prefer options to increase shareholder value so that investor trust in the company will increase and, in turn, this can lead to increased demand for company shares and pushed up share prices and dividends. On the other hand, firm size has a significant negative effect on dividend payout, which indicates that large companies prefer projects that can produce a high rate of return, so the company allocates funds to these projects rather than paying dividends to shareholders.